PLASMA GASIFICATION – THE WASTE-to-ENERGY SOLUTION FOR THE FUTURE - Birsan N. (Problems of the Regional Energetics)
Plasma WtE is currently subject of extensive research and a number of companies across the globe are trying to develop a suitable, eco-friendly and efficient WtE technology for the future. While all of these companies are still working on concept designs or small-scale prototypes, there is one company already building large industrial scale plasma gasifiers around the globe to treat MSW, Industrial and Toxic waste all together. In 1999 in Japan, Hitachi Metals and Westinghouse Plasma Corp (“WPC”) built the World’s First commercial demonstration plasma WtE plant. Hitachi Metals operated the plant for one year on municipal solid waste and obtained a certification from the Japan Waste Research Foundation (JWRF). Subsequently, Hitachi Metals leveraged this success into the two commercial plants at Mihama-Mikata and Utashinai in Japan, both having at the very core the now proven Westinghouse Plasma gasification technology. For more than 20 years, Westinghouse Plasma Corp (WPC) has been leading the technology platform for converting the world’s waste into clean energy for a healthier planet. The WPC technology makes landfills obsolete and replaces Incineration as the primary process for WtE. The WPC technology already operates in three reference plants around the world and other three new commercial plants are under construction (two plants of 1000 tons/day in UK and a 650 tons/day in China), all three designed to convert municipal solid waste to electricity and district heat, in the most efficient and environmental-friendly manner.